PEMETAAN KELEMBAGAAN PEMERINTAH KOTA DALAM PENANGANAN IMIGRAN ILEGAL DI KOTA PEKANBARU - M Ridho Abdullah; Khairul Anwar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
A wave of immigration occurred again in the 20th century. Total global flow of immigrants was massive re-occur after the occurrence of discomfort in the birthplace or place of origin of conflict such as the inability to live a life problem, a civil war, a cease-state, as well as the seizure of territory. Recorded until the current number of immigrants coming to Europe has broken 1 million people, while for immigrants who crossed Indonesia to seek asylum to Australia and Cristmast Island has reached a hundred thousand people. Most of them are citizens of the Muslim majority in the country of origin. The number of immigrants who were arrested in the city of Pekanbaru also highlighted for the attention of the Government.For year 2014 total of immigrants in the city of Pekanbaru reached 299. The role of institutional accommodate Illegal Immigrants become very necessary thing to handle, administer, and maintain their rights to get what they expect. Agencies in the city like Rudenim, Immigration Office, and Kemenkumham and foreign agencies such as IOM and UNHCR become an indispensable institution. who need protection to live and settle. Fear the Illegal Immigrants to return the country of origin makes them not want to come back kenegara origin so that it takes the role of institutions related Illegal Immigrants. Justice must be obtained by the two aspects, namely the institutions involved as well as the illegal immigrants who are victims. Need justice together so that this issue was resolved to get justice.Keywords: Implementation, Single Tuition, University of Riau